Kebebasan dalam Filsafat Eksistensialisme Jean Paul Sartre - Firdaus M. Yunus (Al-Ulum, 2011)
Existentialism puts humans at the center point of all human relationships. It is rooted in an effort to keep a distance with all hegemony to discover the existence and the essence of self. Human must be conscious of his humane to find out the existence of himself (l'Ãªtre-en-soi). Since, it is believed that no other creatures besides humans that exists. Freedom is the essence of human beings; usually humans are always free to create him-self. Humans are free to organize, select and can give meaning to reality.